2004
DOI: 10.1016/j.jphysparis.2005.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Local networks in visual cortex and their influence on neuronal responses and dynamics

Abstract: Networks of neurons in the cerebral cortex generate complex outputs that are not simply predicted by their inputs. These emergent responses underlie the function of the cortex. Understanding how cortical networks carry out such transformations requires a description of the responses of individual neurons and of their networks at multiple levels of analysis. We focus on orientation selectivity in primary visual cortex as a model system to understand cortical network computations. Recent experiments in our labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 78 publications
1
13
0
Order By: Relevance
“…We observed broader orientation tuning near the PWCs; this is consistent with recent studies using multi-electrode array recordings in conjunction with optical imaging in both cats and monkeys22, as well as studies using two-photon calcium imaging16. Other earlier studies reported a uniform distribution of orientation tuning of neuronal spike responses across the orientation map; that is, neurons near the PWCs are tuned to orientation as sharply as those away from PWCs23333435. Our simulation results on both OSIs and HWHHs showed that tuning strength varies widely among neurons near the PWCs (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…We observed broader orientation tuning near the PWCs; this is consistent with recent studies using multi-electrode array recordings in conjunction with optical imaging in both cats and monkeys22, as well as studies using two-photon calcium imaging16. Other earlier studies reported a uniform distribution of orientation tuning of neuronal spike responses across the orientation map; that is, neurons near the PWCs are tuned to orientation as sharply as those away from PWCs23333435. Our simulation results on both OSIs and HWHHs showed that tuning strength varies widely among neurons near the PWCs (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Anatomical evidence suggests that neurons situated close to pinwheel centers are connected with neurons having all preferred orientations whereas neurons located in orientation domains are connected mostly with neurons sharing similar orientation preferences [31]. Along with location in the orientation map, laminar position is a main source of diversity in the inputs to a V1 neuron.…”
Section: Resultsmentioning
confidence: 99%
“…The preponderance of morphological and electrophysiological data predict that in the monkey, synaptic integration at the cellular and network levels differ between V1, a primary sensory area for unimodal representation, and LPFC, a high-order area for complex multimodal processing (review: Schummers et al, 2004; Fuster, 2015). V1 neurons are small, compact and highly excitable, properties that enable them to respond optimally to small, fast synaptic inputs and for building a network with a limited dynamic range but well-suited for signal transformations with relatively high input-output fidelity (review: Olshausen and Field, 2004; Vogels et al, 2005; Panzeri et al, 2010).…”
Section: Implications For Species-specific Cortical Areal Specializationmentioning
confidence: 99%